High-stakes testing: the student experience - Pearson, Timothy, author; Timpson, William M., advisor (Colorado State University. Libraries, 2009)
The accountability components of the No Child Left Behind act of 2002 led to nearly universal high-stakes testing in public schools in the United States. There are a large number of studies and articles related to this testing but little in the literature about how students perceive and understand high-stakes testing. The purpose of this study was to investigate how students experience high-stakes tests. Six tenth grade students were interviewed for this narrative inquiry. Six narratives were constructed using transcript data. Six thematic elements were identified after additional analysis. The first thematic element is School Loyalty and Test Compliance. The participants varying levels of loyalty did not seem to be a factor in their test performance. The second theme is Test as a Measure of the Student. The participants rejected the notion that high-stakes tests defined them as individuals or students. The third thematic element is Personal Relevancy of the Test. Five participants were critical of the test's connection to their current or future lives. The third element is Motivation. Only two students said they were not motivated to perform well on the tests, however, most participants said many of their peers were unmotivated by the assessments. The fourth element is Test Anxiety. Three participants said they were anxious when they took the tests. Two of these said they experienced memory blocks and physical symptoms. The fifth element is Human Connections and the Unknowable They. Most participants said they knew little about the reasons they were tested and about the people responsible for the testing process. They craved a connection with these unknown figures. The sixth thematic element is the Relationship to Silence. Four of the participants said they were uncomfortable with silence in general, and particularly with enforced silence during testing. The researcher suggests further study of some important findings. These include investigating whether student test performance is affected by silence or by having a human connection with test designers. A simulated panel discussion is used as a means to compare and contrast the findings of the study with legislative positions, the views of the researcher and the theories of John Dewey.
Keywords: high-stakes testing; NCLB; narrative inquiry; No Child Left Behind; student assessment; student opinions; educational tests and measurements; curriculum development; students; No Child Left Behind Act 2001-us; public schools